If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(y + -4) + 3y = 26 Reorder the terms: 4(-4 + y) + 3y = 26 (-4 * 4 + y * 4) + 3y = 26 (-16 + 4y) + 3y = 26 Combine like terms: 4y + 3y = 7y -16 + 7y = 26 Solving -16 + 7y = 26 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '16' to each side of the equation. -16 + 16 + 7y = 26 + 16 Combine like terms: -16 + 16 = 0 0 + 7y = 26 + 16 7y = 26 + 16 Combine like terms: 26 + 16 = 42 7y = 42 Divide each side by '7'. y = 6 Simplifying y = 6
| xa+xb+ya+yb=0 | | 7x+1-9=5x | | 7(x+2y-1)= | | 9x+2-(5+4x)=4x+3 | | 1.7x=34 | | -4-7y-10=0 | | 5x+9+2y+x+11+7y= | | 3x=5.7 | | 2x+7-5x=1 | | 5x+7=3x-11 | | x-31=31 | | t^2-4+1=0 | | 3-2x=-1.5 | | y=-9/5x-4/5 | | 5X(1/3)^4 | | 2a-3=3a+2 | | 82=-16t^2+60t+s | | -3.5x^2-2.1x-1=0 | | Y+14=-4x | | 2/x=1/x^2-5 | | 9x^2-29+22=0 | | 9*5-5+5= | | 2-9/x^2=5/x | | 24+3-2X=35 | | 2x+25x=0 | | 4*x+12=24 | | 0.02+x=3.2 | | 14+2n-6+8n=4n-21+3n | | -5-n(1+7n)=-8 | | 4x-3y+5z=18 | | (2sinx-1)-(3cosx-1)=0 | | x^(1/x)=23 |